LINGUISTIC FEATURES OF PHALERONYMIC TERMS IN THE ENGLISH LANGUAGE (Web of Teachers: Inderscience Research, 2025)
This article explores the linguistic features of phaleronymic terms — names of medals, orders, crosses, stars, and other state or institutional decorations — in the English language. As a distinct class of proper names, phaleronyms embody commemorative, evaluative, and honorific functions, while also reflecting English morphological patterns, lexical preferences, and pragmatic conventions. The study highlights their lexical-semantic fields, morphological structures, syntactic behavior, and sociolinguistic functions, with emphasis on how they encode values such as bravery, merit, loyalty, and service. The paper concludes with directions for further comparative research.